1983
DOI: 10.1007/bf03350608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha-1-blockade by prazosin on blood sugar, insulin and glucagon levels in normals and non-insulin dependent diabetics

Abstract: The AA. studied the glycometabolic activity of prazosin, a hypotensive drug with an adrenergic blocking activity of alpha-1-selective type. Twenty-two moderately hypertensive subjects were studied. Their ages ranged from 37 to 57 years; 10 of the patients had non-insulin dependent diabetes mellitus. After overnight fasting every patient underwent an oral glucose test (g 100) at 09:00. Blood samples were withdrawn at 0, 30, 60, 90 and 120 minutes. Each patient was then given in randomized and double-blind fashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In addition, in the present study, CAPA was found to inhibit α-adrenergic receptors on vascular tissue. Since inhibition of sympathetic α-adrenergic receptors is reported to enhance insulin release [52], the stimulation of insulin release by CAPA may be partly attributed to inhibition of α-adrenoceptors. In STZ-induced type 1 diabetic rats, CAPA lowered plasma glucose levels even though this diabetic rat model has low insulin secretion activity, suggesting that insulin-independent mechanisms may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the present study, CAPA was found to inhibit α-adrenergic receptors on vascular tissue. Since inhibition of sympathetic α-adrenergic receptors is reported to enhance insulin release [52], the stimulation of insulin release by CAPA may be partly attributed to inhibition of α-adrenoceptors. In STZ-induced type 1 diabetic rats, CAPA lowered plasma glucose levels even though this diabetic rat model has low insulin secretion activity, suggesting that insulin-independent mechanisms may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with diabetes and hypertension, similar effects have been noted. Several investigators reported that prazosin did not alter glycemic control (229,236), and others found a significant, although small, decrease in GHb levels (76,233) and improved glucose tolerance (232).…”
Section: A-blockersmentioning
confidence: 98%
“…Of the 27 clinical studies evaluating the use of an α 1 ‐blocking agent in patients with type 2 diabetes, 22 were included in the analysis (Table 2). 17,18,20,29–47 In these studies (published between 1980 and 1995), the number of subjects ranged from 5 to 70, and the study duration ranged from 1 week to 21 months (mean 18.8 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies•(Table 2: studies 1, 7, 8, 10, 11, 13, 14, 16,17,19,20,22) reported changes in HDL cholesterol: 11 with doxazosin and one with bunazosin. As shown in Table 3, for all selective a 1 -blockers and for doxazosin alone, the results showed statistically significant increases in HDL cholesterol (mean changes of0.12 and 0.13 mmol/1, respectively).…”
Section: Lipid Parametersmentioning
confidence: 99%
See 1 more Smart Citation